Effects of high-dose vitamin D supplementation on bone mineral density in very low birth weight preterm infants - Yoo, Myoung-Jin; Seo, Jeong Ho; Lee, Inwook; Kim, Hyuna; Choi, Jinjoo; Choe, Yunsoo; Lee, Hyun Ju; Yang, Seung (Frontiers in Endocrinology, 2025)
BackgroundVitamin D deficiency is common among very low birth weight (VLBW) preterm infants due to challenges in achieving adequate enteral nutrition and reduced transplacental transfer. Supplementation with 800 IU/day of vitamin D has been shown to safely and effectively increase serum 25-hydroxyvitamin D [25(OH)D] levels above 30 ng/mL when initiated at two weeks of age and continued until hospital discharge.ObjectiveThis study aimed to evaluate whether daily supplementation with 800 IU of vitamin D significantly improves bone mineral density, as measured by dual-energy X-ray absorptiometry (DEXA), in VLBW infants at discharge, compared to supplementation with 400 IU/day.MethodsWe retrospectively reviewed the medical records of 215 VLBW infants with birth weights under 1,500 g who were admitted to the neonatal intensive care unit at Hanyang University Seoul Hospital between January 2010 and December 2023. The infants were divided into two groups based on their daily vitamin D intake of either 400 IU or 800 IU, initiated on day 14 of life after trophic feeding was established. Bone mineral apparent density (BMAD) was assessed at discharge using whole-body DEXA (Hologic QDR-4500, infant mode).ResultsMaternal age (32.01 ± 3.43 vs. 33.34 ± 4.39 years, p = 0.017) and birth weight (812.86 ± 141.19 vs. 883.76 ± 260.09 g, p = 0.010) were significantly higher in the 800 IU group, which also had a longer duration of total parenteral nutrition. After adjusting for birth weight and duration of parenteral nutrition, total body BMAD was significantly higher in the 800 IU group (p = 0.008). A general linear model further demonstrated that 800 IU supplementation was positively associated with femoral BMAD at discharge (β = 0.267, p= 0.001).ConclusionDaily supplementation of 800 IU of vitamin D was associated with improved bone mineralization, as measured by DEXA, at discharge in VLBW infants.